2022
DOI: 10.1177/09636897221125685
|View full text |Cite
|
Sign up to set email alerts
|

Designing Olfactory Ensheathing Cell Transplantation Therapies: Influence of Cell Microenvironment

Abstract: Olfactory ensheathing cell (OEC) transplantation is emerging as a promising treatment option for injuries of the nervous system. OECs can be obtained relatively easily from nasal biopsies, and exhibit several properties such as secretion of trophic factors, and phagocytosis of debris that facilitate neural regeneration and repair. But a major limitation of OEC-based cell therapies is the poor survival of transplanted cells which subsequently limit their therapeutic efficacy. There is an unmet need for approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 156 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Pharmaceutical agents targeting RhoA/ROCK and other signaling pathways have also shown potential [ 105 , 106 ]. Additionally, cell transplantation strategies offer promising avenues to modulate the glial scar environment [ 107 , 108 , 109 , 110 ].…”
Section: Current Challenges In the Treatment Of Scismentioning
confidence: 99%
“…Pharmaceutical agents targeting RhoA/ROCK and other signaling pathways have also shown potential [ 105 , 106 ]. Additionally, cell transplantation strategies offer promising avenues to modulate the glial scar environment [ 107 , 108 , 109 , 110 ].…”
Section: Current Challenges In the Treatment Of Scismentioning
confidence: 99%
“…However, a common consequence in these studies is the poor survival of transplanted cells, with survival rates ranging from 0.3 percent to 3 percent. This issue is probably related to the fact that when OECs are isolated, expanded in vitro, and then transplanted into the injury site, their therapeutic potential is reduced, probably due to bleeding, damaged tissue and anatomical structures and hostile microenvironment present in the lesioned area (115)(116)(117). Therefore, in vitro models challenging OECs, by mimicking the injured tissue microenvironment, are needed.…”
Section: Oecs For Tissue Regeneration and Transplantationmentioning
confidence: 99%
“…For example, it has been found that preconditioned OECs showed increased migratory, phagocytic and immunomodulatory capacities. To improve their efficacy and yield upon graft, cells could be then exposed to a low oxygen level, or they could grow into three-dimensional scaffolds before being transplanted into the lesion ( 116 ).…”
Section: Oecs For Tissue Regeneration and Transplantationmentioning
confidence: 99%
“…Cell transplantation is one of the most promising strategies for the repair of central nervous system (CNS) injuries. Many studies have shown that transplantation of olfactory ensheathing cells (OECs) can induce axon regeneration, remyelination, and restoration of function in experimental spinal cord injuries 1 12 . Our previous studies showed that transplantation of cultured bulbar OECs in rats to bridge transected dorsal roots to the spinal cords induced the regeneration of axons and restored directed forepaw reaching and vertical climbing functions 6 , 13 .…”
Section: Introductionmentioning
confidence: 99%